Boosting Vascular Imaging‐Performance and Systemic Biosafety of Ultra‐Small NaGdF4 Nanoparticles via Surface Engineering with Rationally Designed Novel Hydrophilic Block Co‐Polymer. Issue 3 (2nd February 2022) - Jiang, Zhilin; Xia, Bin; Ren, Feng; Bao, Bolin; Xing, Wei; He, Tao; Li, Zhen
Abstract: Revealing the anatomical structures, functions, and distribution of vasculature via contrast agent (CA) enhanced magnetic resonance imaging (MRI) is crucial for precise medical diagnosis and therapy. The clinically used MRI CAs strongly rely on Gd‐chelates, which exhibit low T 1 relaxivities and high risks of nephrogenic systemic fibrosis (NSF) for patients with renal dysfunction. It is extremely important to develop high‐performance and safe CAs for MRI. Herein, it is reported that ultra‐small NaGdF4 nanoparticles (UGNs) can serve as an excellent safe MRI CA via surface engineering with rationally designed novel hydrophilic block co‐polymer (BPn ). By optimizing the polymer molecular weights, the polymer‐functionalized UGNs (i.e., UGNs‐BP14 ) are obtained to exhibit remarkably higher relaxivity (11.8 mm –1 s –1 at 3.0 T) than Gd‐DTPA (3.6 mm –1 s –1 ) due to their ultracompact and abundant hydrophilic surface coating. The high performance of UGNs‐BP14 enables us to sensitively visualize microvasculature with a small diameter of ≈0.17 mm for up to 2 h, which is the thinnest blood vessel and the longest time window for low field (1.0 T) MR angiography ever reported, and cannot be achieved by using the clinically used Gd‐DTPA under the same conditions. More importantly, renal clearable UGNs‐BP14 show lower risks of inducing NSF in comparison with Gd‐DTPA due to their negligible release of Gd 3+ ions after modification with the novel hydrophilic block copolymer. The study presents a novel avenue for boosting imaging‐performance and systemic biosafety of UGNs as a robust MRI CA with great potential in precise diagnosis of vasculature‐related diseases. Abstract : Ultra‐small NaGdF4 nanoparticles are engineered with block copolymer into robust magnetic resonance imaging contrast agents with high imaging performance and excellent biosafety. The resultant renal clearable nanoagents exhibit remarkably higher relaxivity (11.8 mm –1 s –1 at 3.0 T) than clinical agent Gd‐DTPA (3.6 mm –1 s –1 ), and negligible release of Gd 3+ ions which significantly reduce the risks of nephrogenic systemic fibrosis.